Design of iron bird for a regional jet aircraft. (March 2020) - Li, Dawei; Lin, Mingxing; Tian, Liang
A regional jet's iron bird was built for trouble shooting and design improvement of its airborne system. Modular design architecture and overall plan for the iron bird were proposed, and structure of the test rig, main tested systems, relevant supporting test systems and test programs were described. Besides, as one of the most critical airborne systems, NLG loading system was chosen for deep research; its mathematical model was built and analyzed in detail. Test results of hydraulic system's main parameters were given. The whole iron bird provided important guarantee for system testing and continued design improvement. Also, test validation level for multi systems integration and fault diagnosis level of airborne system were improved.